DIFFERENTIATED INSTRUCTION THROUGH CHOICE-MAKING TO ENHANCE ENGAGEMENT IN EARLY CHILDHOOD EDUCATION - Novitasari, Nurul; Fitri, Nur Lailatul; Anggraeni, Melinda Dwi Safitri (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2025)
Please Early childhood learners possess diverse characteristics in terms of interests, learning styles, and developmental readiness. However, instructional practices in many early childhood education settings often remain uniform, limiting opportunities for children to engage in activities aligned with their individual needs. This study explores the implementation of differentiated instruction through choice-making as a strategy to enhance children’s engagement and reduce disruptive behaviors in early learning settings. Employing a descriptive qualitative approach, the study was conducted at TK PKK I Bangilan Tuban with one teacher, 15 children aged 4–5 years, the school principal, and three parents as participants. Data were collected through participant observation, semi-structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model with triangulation to ensure validity. Findings indicate that differentiated instruction was carried out in three stages: preparation (diagnostic assessment of readiness, interests, and learning styles), implementation (differentiated content, process, and product), and evaluation-reflection. The results show that choice-making strategies significantly increased children’s active participation, focus, and enthusiasm during learning activities, while also reducing instances of tantrums and passive behavior. Children demonstrated greater autonomy, motivation, and positive emotional regulation when provided with meaningful options. This study concludes that differentiated instruction integrated with choice-making not only supports cognitive, social, and emotional development, but also fosters an inclusive, engaging, and equitable learning environment. The findings have theoretical implications for enriching the literature on differentiated instruction and practical implications for PAUD teachers in designing flexible, child-centered learning strategies.